Design and Synthesis of (2,3-dichloro-4-(3-(substituted Phenyl)acryloyl)phenoxy) Substituted Carboxylic Acid as Potent Glutathione-s-transferase Inhibitors, Anti-breast-cancer Agents and Enhancing Therapeutic Efficacy of Anticancer Agents - Qayyum, Afreen Begum Abdul; Ali, Syed Ayaz; Mokale, Santosh Namdeo (Medicinal Chemistry, 2025)
BackgroundEthacrynic acid is a dynamic agent holding alpha-beta unsaturated carbonyl unit in its structure which imparts superiority and extraordinary advantage of displaying multiple biological activities such as anticancer, antiviral, anti-malarial effect, diuretic effect and inhibits the Glutathione-s-transferase p1-1 enzyme which produces hindrance in the pathway of apoptosis. Ethacrynic acid is an inhibitor of Glutathione-s-transferases. EtA by itself act as an anti-cancer agent at higher concentration and also increases effectiveness of other compounds used in cancer treatment by preventing their detoxification, all these facts attracted our attention to develop and evaluate novel structural analogues of ethacrynic acid for their inhibitory effect on GSTs and anti-cancer activity in breast cancer.ObjectiveBy attending rational drug design perspectives the research is aimed to develop and evaluate novel structural analogues of ethacrynic acid as Inhibitors of GSTs enzyme and with anti-breast cancer activity.MethodsDesigned compounds were synthesized as per convenient route shown in the scheme of synthesis. Molecular docking studies were done against GSTP1-1 (PDB:3HJO). Structures of novel synthesized molecules were confirmed by spectral characterization such as FTIR, 1HNMR, 13CNMR and Mass spectrometry. ADME studies were done to ensure safety and drug like properties of the compounds. Ten structural analogues of ethacrynic acid were synthesized and evaluated for their inhibitory effect on activity of Glutathione-s-transferases which was measured by performing assay method. In-vitro anti-breast cancer activity was done on MCF-7 and MDAMB-231 cell line by MTT assay.ResultsCompound A3, A5 and A6 were found with greater inhibition of the activity of GSTs and maximum anti-proliferative activity in breast cancer.ConclusionWe have effectively developed novel compounds possessing structural resemblance with ethacrynic acid Compounds of the series has shown moderate to higher inhibitory effect on GSTs and anti-proliferative activity in breast cancer. The compound A3 was found to be promising agent with high level of potency in each biological response. The research studies presented here may be an enlightening path in development of novel therapeutic agents with high level of inhibition in the activity of GSTs and anti-breast cancer effect.
Keywords: GSTs